INDONESIAN TEACHER PERFORMANCE: Professional and Character - Baety, Nur (Perhimpunan Sarjana Ekonomi dan Bisnis, 2021)
Teacher is a profession that demands competence, professionalism, and role model. This task is very heavy, so there needs to be special and more attention from the education unit organizers, even the government. On the shoulders of the teacher is the fate of the nation in the future, by providing quality education to the nation's children. This study aims to review teacher performance through its main determinants, namely professional and personality. In order to answer the research objectives, this research uses a quantitative scientific approach with regression analysis techniques. The object of research is a religious school in the Kuningan area, West Java. The research sample is teachers, as many as 125 people. The research data was obtained through questionnaires, either through google forms or questionnaire sheets. The results of the study reveal that teacher performance is very important for student success. Therefore, professional and personality factors are very decisive, how teachers educate and guide students to be able to excel and have character. Interestingly, the contribution of teacher performance also has an impact on the quality of educational institutions.